#ShutItAllDown social protest: Examining emotional content on Twitter against sexual gender-based violence in Namibia - Anthony Eniayejuni (Faculty of Social and Political Science, Universitas Airlangga, 2023)
Over the years, social media has evolved into the primary platform for political activism. Citizens have utilized social media platforms to mobilize people to band together and rise against injustice. Social protests usually occur because of citizens’ emotional reactions to perceptions of injustice. Citizens have traditionally used social protests to voice their dissatisfaction with government policies and to influence political reforms. Citizens’ participation in social protests is fraught with emotion. Emotions elicited by political stimuli play a vital role in initiating and guiding goal-directed behavior. Therefore, this study intends to analyze the emotions expressed in Twitter posts during the #ShutItAllDown social protest. This study uses a quantitative approach. The findings show that both positive and negative emotions expressed on social media accelerate Namibian youth participation in the #ShutItAllDown social protests. Fear, anger, and anticipation instigate people’s participation in protests, whereas joy and happiness are feelings of satisfaction that are experienced during goal achievement. Thus, protest participation arising from both positive and negative emotions enforces government reforms.